META-ANALISIS PENELITIAN TENTANG PROBLEM BASED LEARNING PADA TAHUN 2013-2018 - Uray Ade Firmansyah; Edy Tandililing; Syukran Mursyid (Universitas Tanjungpura, 2022)
Abstrak The Reaserch aim: (1) To measure the effect of Problem Based Learning (PBL) learning on physics learning based on education level. (2) To measure the influence of Problem Based Learning (PBL) on physics learning by region. (3) To measure the effect of Problem Based Learning (PBL) learning on physics learning based on the dependent variable. This Research method is a quantitative descriptive method. The effect of studies that apply PBL learning is analyzed using meta-analysis techniques. By the stated rescuers objectives, the subjects in this research were obtained from a review of 10(ten) research reports. the research findings reveal that overall the studies carried out are influential an effective on the physics learning outcomes of students with an effect size of 2,064 or in the high category. The PBL model also provides influence and is effective in term of are, level of education and application of learning to improve problem-solving skills, mastery of concepts, learning outcomes, misconceptions, and high order thinking skills. This reseals concludes that the Problem Based Learning is effective for improving problem-solving skills, mastery of concepts, learning outcomes, misconceptions, and high order thinking skills.